Archetípusos pszichológiai reprezentáció az Özvegy és leányában - Bényei, Péter (Studia Litteraria, 2014)
The essay focuses on the psychological processes staged in Zsigmond Kemény’s The Widow and the Daughter: on the one hand, the personality changing aspects of the archetypal framework, on the other hand, the psychological representation of the mother-daughter relationship. The events that take place in the novel can be integrated into a more or less seamless psychological narrative. The archetype materialized in one of the protagonists of the novel, Madame Tarnóczi, overlaps with the psychological phenomenon that Shinoda Bolen called the Hera-archetype. The loss of balance in her marriage leads to serious mental problems: Madame Tarnóczi’s emotional-mental state of being offended and resentful becomes permanent, and that results in the suspension of her maternal instincts. Her thirst for revenge – due to her archetypical compulsion – is transferred to her daughter, who commits suicide to escape the unbearable psychological pressure. The representation of the deformed mother-daughter relationship seems exemplary in the novel, and in this respect the novel appears more responsive than it used to be in its own age.